Urgensi Upaya Menjaga Mutu Pembelajaran di Tengah Pandemi Covid 19 - Imam Subhi (STAI Bumi Silampari, 2020)
This study aims to get a description of efforts to maintain the quality of learning in the midst of the covid pandemic 19. The research method used is literature study with analytical techniques in the form of content analysis. The results of this study are that the government has done to maintain the quality of learning by promoting the concept of independent learning proclaimed by the Ministry of Education and Culture, then strengthened with a joint decree covering the Ministry of Education and Culture, Ministry of Religion, Ministry of Health and Ministry of Foreign Affairs concerning guidelines for organizing learning in the year new academic teachings during the pandemic corona virus disease (Covid-19), and in its realization strengthened by the issuance of covid 19 emergency curriculum guidelines by the Directorate General of Islamic Education the Ministry of Religion published curriculum guidelines during Covid-19 emergencies for Madrasah. This guide is listed in the Decree of the Director General of Islamic Education Ministry of Religion. The guide actually provides an open space for learning managers to be able to accurately determine learning targets. The three efforts are expected to maintain the quality of learning even if they are not able to run optimally.